# HSSlive: Plus One & Plus Two Notes & Solutions for Kerala State Board

## BSEB Class 9 Maths Chapter 2 Polynomials Ex 2.4 Textbook Solutions PDF: Download Bihar Board STD 9th Maths Chapter 2 Polynomials Ex 2.4 Book Answers BSEB Class 9 Maths Chapter 2 Polynomials Ex 2.4 Textbook Solutions PDF: Download Bihar Board STD 9th Maths Chapter 2 Polynomials Ex 2.4 Book Answers

BSEB Class 9th Maths Chapter 2 Polynomials Ex 2.4 Textbooks Solutions and answers for students are now available in pdf format. Bihar Board Class 9th Maths Chapter 2 Polynomials Ex 2.4 Book answers and solutions are one of the most important study materials for any student. The Bihar Board Class 9th Maths Chapter 2 Polynomials Ex 2.4 books are published by the Bihar Board Publishers. These Bihar Board Class 9th Maths Chapter 2 Polynomials Ex 2.4 textbooks are prepared by a group of expert faculty members. Students can download these BSEB STD 9th Maths Chapter 2 Polynomials Ex 2.4 book solutions pdf online from this page.

## Bihar Board Class 9th Maths Chapter 2 Polynomials Ex 2.4 Books Solutions

 Board BSEB Materials Textbook Solutions/Guide Format DOC/PDF Class 9th Subject Maths Chapter 2 Polynomials Ex 2.4 Chapters All Provider Hsslive

## How to download Bihar Board Class 9th Maths Chapter 2 Polynomials Ex 2.4 Textbook Solutions Answers PDF Online?

2. Click on the Bihar Board Class 9th Maths Chapter 2 Polynomials Ex 2.4 Answers.
3. Look for your Bihar Board STD 9th Maths Chapter 2 Polynomials Ex 2.4 Textbooks PDF.
4. Now download or read the Bihar Board Class 9th Maths Chapter 2 Polynomials Ex 2.4 Textbook Solutions for PDF Free.

Find below the list of all BSEB Class 9th Maths Chapter 2 Polynomials Ex 2.4 Textbook Solutions for PDF’s for you to download and prepare for the upcoming exams:

## BSEB Bihar Board Class 9th Maths Solutions Chapter 2 Polynomials Ex 2.4

Question 1.
Determine which of the following polynomials has (x + 1) a factor:
(i) x³ + x² + x + 1
(ii) x4 + x³ + x² + x + 1
(iii) x4 + 3x³ + 3x² + x + 1
(iv) x³ – x² – (2 + 2‾√)x + 2‾√
Solution:
(i) In order to prove that x + 1 is a factor of p(x) = x³ + x² + x + 1, it is sufficient to show that p(- 1) = 0.
Now, p(- 1) = (- 1)³ + (- 1)² + (- 1) + 1
= – 1 + 1 – 1 + 1 = 0
Hence, (x + 1) is a factor of pix) = x³ + x² + x + 1.

(ii) In order to prove that (x + 1) is a factor of
p(x) = x4 + x³ + x² + x + 1, it is sufficient to show that p(- 1) = 0.
Now, p(- 1) = (- 1)4 + (- 1)3 + (- 1)² + (- 1) + 1
= 1 – 1 + 1 – 1 + 1 = 1 ≠ 0
∴ (x + 1) is not a factor of x4 + x³ + x² + x + 1.

(iii) In order to prove that (x + 1) is a factor of
p(x) = x4 + 3x³ + 3x² + x + 1, it is sufficient to show that p(- 1) = 0.
Now, p(- 1) = (- 1)4 + 3(- 1)3 + 3(- 1)² + (- 1) + 1
= 1 – 1 + 1 – 1 + 1 = 1 ≠ 0
∴ (x + 1) is not a factor of x4 + x³ + x² + x + 1.

(iv) In order to prove that (x + 1) is a factor of
p(x) = x³ – x² – (2 + 2‾√)x + 2‾√, it is sufficient to show that p(- 1) = 0.
Now, p(- 1) = (- 1)3 – (- 1)² + (2 + 2‾√)(- 1) + 2‾√
= 1 – 1 + 2 + 2‾√ + 2‾√ = 22‾√ ≠ 0
∴ (x + 1) is not a factor of x³ – x² (2 + 2‾√)x + 2‾√.

Question 2.
Use the Factor Theorem to determine whether g(x) is a factor of p(x) in each of the following cases :
(i) p(x) = 2x³ + x² – 2x – 1, g(x) = x + 1
(ii) p(x) = x³ + 3x² + 3x + 1, g(x) = x + 2
(iii) p(x) = x³ – 4x² + x + 6, g(x) = x – 3
Solution:
(i) In order to prove that g(x) = x + 1 is a factor of p(x) = 2x³ + x² – 2x – 1, it is sufficient to show that p(- 1) = 0
Now, p(- 1) = 2(- 1)³ + (- 1)² – 2(- 1) – 1
= – 2 + 1 + 2 – 1 = 0
∴ g(x) is a factor of p(x).

(ii) In order to prove that gix) = x + 2 is a factor of p(x) = x³ + 3x² + 3x + 1, it is sufficient to show that p(- 2) = 0
Now, p(- 2) = (- 2)³ + 3(- 2)² – 3(- 2) – 1
= – 8 + 12 – 6 + 1
= – 1 ≠ 0
∴ g(x) is a factor of p(x).

(iii) In order to prove that gix) = x – 3 is a factor of pix) = x³ – 4x² + x – 6, it is sufficient to show that p(+ 3) = 0
Now, p(3) = (3)³ – 4(3)² + 3 – 6
= 27 – 36 + 3 – 6 = 0
= – 12 ≠ 0
∴ g(x) is a factor of p(x).

Question 3.
Find the value of k, if x – 1 is a factor of pix) in each of the following cases:
(i) p(x) = x² + x + k
(ii) p(x) = 2x² + kx + 2‾√
(iii) p(x) = kx² – 2‾√x + 1
(iv) p(x) = kx² – 3x + k
Solution:
(i) If (x – 1) is a factor of pix) = x² + x + k, then
p(1) = 0
⇒ (1)² + 1 + k = 0
⇒ 1 + 1 + k = 0
⇒ k = – 2

(ii) If (x – 1) is a factor of p(x) = 2x² + kx + 2‾√, then
p(1). = 0
⇒ 2(1)² + k(1) + 2‾√ = 0 ⇒ 2 + k + 2‾√ = 0
⇒ k = – (2 + 2‾√)

(iii) If (x – 1) is a factor of p(x) = kx² – 2‾√x + 1, then
p(1) =0
⇒ k(1)² – 2‾√ (1) + 1 = 0 ⇒ k – 2‾√ + 1 = 0
⇒ k = 2‾√ – 1

(iv) If (x – 1) is a factor of p(x) = kx² – 3x + k, then
p(1) = 0
⇒ k(1)² – 3(1) + k = 0 = k – 3 + k = 0
2A = 3 ⇒ k = 32

Question 4.
Factories :
(i) 12x² – 7x + 1
(ii) 2x² + 7x + 3
(iii) 6x² + 5r – 6
(iv) 3x² – x – 4
Solution:
(i) Here p + q = coeff. of x = – 7
pq = coeff.of x² x constant term =
= 12 x 1 = 12
∴ P + q = – 7 = – 4 – 3
and pq = 12 = (- 4)(- 3)
∴ 12x² – 7x + 1 = 12x² – 4x – 3x + 1
= 4x(3x – 1) – 1(3x – 1)
= (3x – 1)(4x – 1)

(ii) Here p + q = coeff. of x = 7
pq = coeff. of x² x constant term
= 2 x 3 = 6
∴ p + q = 7 = 1 + 6
pq = 6 = 1 x 6
∴ 2x² + 7x + 3 = 2x² + x + 6x + 3
= x(2x + 1) + 3(2x + 1)
= (2x + 1)(x + 3)

(iii) Here p + q = coeff. of % = 5
pq = coeff. of x² x constant term
= 6 x – 6 = – 36
p + q = 5 = 9 + (- 4)
and pq = – 36 = 9 x (- 4)
∴ 6x² + 5x – 6 = 6x² + 9x – 4x – 6
= 3x(2x + 3) – 2(2x + 3)
= (2x + 3)(3x – 2)

(iv) Here p + q = coeff. of x = – 1
pq = coeff. of x² x constant term
= 3 x – 4 = – 12
∴ P + q = – 1 = 3 + (- 4)
and pq = – 12 = 3 x (- 4)
∴ 3x² – x – 4 = 3x + 3x – 4x – 4
= 3x(x + 1) – 4(x + 1)
= (x + 1)(3x – 4)

Question 5.
Factorise :
(i) x³ – 2x² – x + 2
(ii) x³ – 3x² – 9x – 5
(iii) x³ + 32x² + 32x + 20
(iv) 2y³ + y² – 2y – 1
Solution:
(i) Let f(x) = x³ – 2x² – x + 2
The constant term in fhc) is + 2 and factors of – 2 are ± 1, ± 2.
Putting x = 1 in f(x), we have
f(1) = (1)³ – 2(1)² – 1 + 2
= 1 – 2 – 1 + 2 = 0
∴ (x – 1) is a factor of fix).
Putting x = – 1 in f(x), we have
f(- 1) = (- 1)³ – 2(- 1)² – ( – 1) + 2
= – 1 – 2 + 1 + 2 = o
∴ x + 1 is a factor of f(x).
Putting x = 2 in f(x), we have
f(2) = (2)³ – 2(2)² – (2) + 2
= 8 – 8 – 2 + 2 = 0
∴ (x + 2) is a factor of f(x)
Putting x = – 2 in fix), we have
f(- 2) = (- 2)³ – 2(- 2)² – (- 2) + 2
= – 8 – 8 + 2 + 2
= – 12 ≠ 0
∴ x + 2 is not a factor of fix).
∴ The factors of f(x) are (x – 1), (x + 1) and (x – 2).
Let f(x) = k(x – 1)(x + 1)(x – 2)
⇒ x³ – 2x² – x + 2 = k(x – 1)(x + 1)(x – 2)
Putting x = 0 on both sides, we have
2 = k(- 1)(1)(- 2) ⇒ k = 1
x³ – 2x² – x + 2 = (x – 1)(x + 1)(x – 2)

(ii) Let p(x) = x³ – 3x² – 9x – 5
We shall look for all factors of – 5. These are ± 1, ± 5.
By trial, we find p(- 1) = – 1 – 3 + 9 – 5 = 0. So, (x + 1) is a factor of p(x). ∴ p(x) = (x + 1)(x² – 4x – 5)
= (x + 1)(x² + x – 5x – 5)
= (x + 1)[x(x + 1) – 5(x + 1)]
= (x + 1)(x + 1)(x – 5)

(iii) Let p(x) = x³ + 13x² + 32x + 20 .
We shall look for all facotrs of + 20, these are + 1, ± 2, ± 4, ± 5, ± 10 and ± 20.
By trial, we find
p(- 2) = – 8 + 52 – 64 + 20 = 0
∴ (x + 2) is a factor of p(x)
Now, divide p(x) by x + 2. ∴ p(x) = (x + 2)(x² + 11x + 10)
= (x + 2)(x² + x + 10x + 10)
= (x + 2)[x(x + 1) + 10(x + 1)]
= (x + 2)(x + 1)(x + 10)

(iv) Let p(y) = 2y³ + y² – 2y – 1
By trial, we find p(1) = 2 + 1 – 2 – 1 = 0.
So, (y – 1) is a factor of p(y).
Now, divide p(y) by y – 1 ∴ p(y) = (y – 1)(2y² + 3y + 1)
= (y – 1)(2y² + 2y + y + 1)
= (y – 1)[2y(y + 1) + 1(y + 1)]
= (y – 1)(y + 1)(2y + 1)

## Bihar Board Class 9th Maths Chapter 2 Polynomials Ex 2.4 Textbooks for Exam Preparations

Bihar Board Class 9th Maths Chapter 2 Polynomials Ex 2.4 Textbook Solutions can be of great help in your Bihar Board Class 9th Maths Chapter 2 Polynomials Ex 2.4 exam preparation. The BSEB STD 9th Maths Chapter 2 Polynomials Ex 2.4 Textbooks study material, used with the English medium textbooks, can help you complete the entire Class 9th Maths Chapter 2 Polynomials Ex 2.4 Books State Board syllabus with maximum efficiency.

## FAQs Regarding Bihar Board Class 9th Maths Chapter 2 Polynomials Ex 2.4 Textbook Solutions

#### Can we get a Bihar Board Book PDF for all Classes?

Yes you can get Bihar Board Text Book PDF for all classes using the links provided in the above article.

## Important Terms

Bihar Board Class 9th Maths Chapter 2 Polynomials Ex 2.4, BSEB Class 9th Maths Chapter 2 Polynomials Ex 2.4 Textbooks, Bihar Board Class 9th Maths Chapter 2 Polynomials Ex 2.4, Bihar Board Class 9th Maths Chapter 2 Polynomials Ex 2.4 Textbook solutions, BSEB Class 9th Maths Chapter 2 Polynomials Ex 2.4 Textbooks Solutions, Bihar Board STD 9th Maths Chapter 2 Polynomials Ex 2.4, BSEB STD 9th Maths Chapter 2 Polynomials Ex 2.4 Textbooks, Bihar Board STD 9th Maths Chapter 2 Polynomials Ex 2.4, Bihar Board STD 9th Maths Chapter 2 Polynomials Ex 2.4 Textbook solutions, BSEB STD 9th Maths Chapter 2 Polynomials Ex 2.4 Textbooks Solutions,
Share: